Analysis of the Conduct of the USA Elections From 2012 to 2024 - Arakaza, Dionise (European Scientific Journal, ESJ, 2025)
The United States held four presidential elections between 2012 and 2024, facing multiple political changes while maintaining secure democratic systems. Voting behavior and electoral management tools like voting rights law modifications determine how elections take place. Every election term had new obstacles and improvements to preserve a fair system as Americans changed what they wanted their Democracy to do. President Barack Obama won a second term in 2012 after making a recovery and healthcare expansion his major campaign issues. During the 2016 presidential elections, Donald Trump became president because he appealed to populism and criticized the political system. The US public cast votes in record numbers during 2020, even with COVID-19 present, which earned Joe Biden victory and brought back a need to unite Americans behind crucial public health initiatives. The 2024 election showed how deep political divisions in America changed the way candidates ran their campaigns, as Donald Trump won the election against Kamala Harris. Political shifts between Democrats and Republicans are two major political parties in the United States that receive support from institutional systems that keep the country stable, even with party disagreements. In all four presidential elections, the election process has been peaceful, which presents the ground for other countries to learn from the United States. Dissecting election results unveils how political parties manage campaigns along with the ruling party’s strengths and limitations to help other countries uphold democratic standards during votes.